2013
DOI: 10.1016/j.mcn.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Calpain-mediated degradation of MDMx/MDM4 contributes to HIV-induced neuronal damage

Abstract: Neuronal damage in HIV-associated Neurocognitive Disorders (HAND) has been linked to inflammation induced by soluble factors released by HIV-infected, and non-infected, activated macrophages/microglia (HIV M/M) in the brain. It has been suggested that aberrant neuronal cell cycle activation determines cell fate in response to these toxic factors. We have previously shown increased expression of cell cycle proteins such as E2F1 and phosphorylated pRb in HAND midfrontal cortex in vivo and in primary neurons expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…A previous study observed a small, but significant increase in MDMx mRNA in patients with AD, but this change did not associate with changes in plaque density or Braak staging [55]. Our results suggest that MDMx regulation may be occurring primarily at the protein level in the CNS, as we and others have reported previously [42, 43]. The reductions in protein expression and increases in mRNA levels suggest that a compensatory mechanism may be at play.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…A previous study observed a small, but significant increase in MDMx mRNA in patients with AD, but this change did not associate with changes in plaque density or Braak staging [55]. Our results suggest that MDMx regulation may be occurring primarily at the protein level in the CNS, as we and others have reported previously [42, 43]. The reductions in protein expression and increases in mRNA levels suggest that a compensatory mechanism may be at play.…”
Section: Discussionsupporting
confidence: 67%
“…The mediator of MDMx degradation is dependent on the insult and the class of proteases subsequently activated by that stress, including caspases, calpains and the proteasome, as shown previously in neurons and in dividing cells [42, 43, 52]. Caspase and calpain activation are not mutually exclusive mechanisms leading to neuronal death, and our results suggest that MDMx degradation may be one point of crosstalk between these two pathways, as MDMx loss is associated with calpain-dependent neuronal damage [43, 53]. …”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…MDM4 is another representative example showing a positive and high-ranked delta Gini (value=0.36; rank=22), but a low-ranked dC (value=0.92; rank=235). This gene was recently demonstrated to be a direct calpain substrate playing roles in the HIV-induced neuronal damage [16]. The detailed values of delta Gini and dC for all comparisons of GCNs of HIV-1 infection were listed in Supplemental Table 1.…”
Section: Application Of Gini Coefficient To Measure the Inequality Ofmentioning
confidence: 99%